DETERMINING FACTORS WHICH COULD AFFECT GUESTS’ WILLINGNESS TO STAY IN A HOTEL DURING THE PANDEMIC - Nicholas Wilson (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2022)
Hotel industry had certainly become one of a few sector which had been affected by the current pandemic situation in a negative way, considering that the travel restriction policies implemented by countries all around the world had significantly reduced the number of tourists visiting and staying in Indonesia. Furthermore, the Community Activities Restrictions Enforcement policy utilized by the Indonesian government had also driven a lot of Indonesians to conduct their work, study and daily activities from inside their own home, thus reducing the number of Indonesians who travel domestically to the other cities or regions in Indonesia, which in turns also reducing the number of domestic guests staying at any hotels in Indonesia. However, many countries’ decision to lift their travel restriction policies starting from the beginning of 2022 had allowed many people to resume their travel activities to the other countries, including to Indonesia, which in turns could increase the number of both domestic and foreign guests staying in the hotels all across Indonesia. Therefore, the objective of this study was to determine the effect given by several factors, namely subjective norm and attitude, in determining people’s willingness to stay in a hotel in the middle of the pandemic situation. Conducted in Indonesia, this quantitative-survey study used questionnaires to gather all data from the respondents. Respondents were individuals’ who’ve ever stayed in any 4-star or 5-star hotels in Indonesia at least once starting from January 01st 2021. There are a total of 188 respondents who filled the questionnaire, in which, these data will later be analyzed using PLS. Based on the results of the data analyses, authors concluded that subjective norm and attitude play significant and positive role in affecting guests’ willingness to stay in the hotels in Indonesia during the pandemic.